Calibration sources for the LEGEND-200 experiment. (1st February 2023) - Baudis, L.; Benato, G.; Bond, E.M.; Chiu, P.J.; Elliott, S.R.; Massarczyk, R.; Meijer, S.J.; Müller, Y.
Abstract: In the search for a monochromatic peak as the signature of neutrinoless double beta decay an excellent energy resolution and an ultra-low background around the Q -value of the decay are essential. The LEGEND-200 experiment performs such a search with high-purity germanium detectors enriched in 76 Ge immersed in liquid argon. To determine and monitor the stability of the energy scale and resolution of the germanium diodes, custom-made, low-neutron emission 228 Th sources are regularly deployed in the vicinity of the crystals. Here we describe the production process of the 17 sources available for installation in the experiment, the measurements of their alpha- and gamma- activities, as well as the determination of the neutron emission rates with a low-background LiI(Eu) detector operated deep underground. With a flux of ( 4.27 ± 0.60stat ± 0.92syst ) × 10 -4  n / (kBq·s), approximately one order of magnitude below that of commercial sources, the neutron-induced background rate, mainly from the activation of 76 Ge, is negligible compared to other background sources in LEGEND-200.